2019
DOI: 10.1002/pssa.201900103
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Optically Stimulated Luminescence in Lu3Al5O12:Ce

Abstract: Lutetium aluminum garnet, commonly known as LuAG, is a versatile material finding numerous optical applications, and whose scintillation properties have been widely investigated. In this study, experimental evidences of optically stimulated luminescence (OSL) phenomena occurring in LuAG:Ce crystals are shown. After demonstrating the possibility to optically bleach an electron trap responsible for a thermally stimulated luminescence (TSL) peak at 280 C (heating rate 1.7 C s À1 ) using red light, a direct measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Apart from the scintillation applications, YAG:Ce and LuAG:Ce crystals with ρ = 4.5 g/cm 3 ; Z eff = 35 and ρ = 6.75 g/cm 3 ; Z eff = 59, respectively, recently emerged as possible alternative materials for TL dosimetry due to high TSL signal and good position of main glow peak in the 250–300 K range after irradiation of different types of ionization radiation [ 7 , 12 , 13 ]. Moreover, the TSL and OSL properties of YAG:Ce and LuAG:Ce crystals were considered in detail [ 7 , 9 , 12 , 14 , 15 ]. Due to such properties, YAG:Ce and LuAG:Ce crystals can be a good candidates for radiative and chemical resistant detectors with small volume and high spatial resolution [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the scintillation applications, YAG:Ce and LuAG:Ce crystals with ρ = 4.5 g/cm 3 ; Z eff = 35 and ρ = 6.75 g/cm 3 ; Z eff = 59, respectively, recently emerged as possible alternative materials for TL dosimetry due to high TSL signal and good position of main glow peak in the 250–300 K range after irradiation of different types of ionization radiation [ 7 , 12 , 13 ]. Moreover, the TSL and OSL properties of YAG:Ce and LuAG:Ce crystals were considered in detail [ 7 , 9 , 12 , 14 , 15 ]. Due to such properties, YAG:Ce and LuAG:Ce crystals can be a good candidates for radiative and chemical resistant detectors with small volume and high spatial resolution [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that scintillating materials of the garnet family may also exhibit interesting properties of optically stimulated luminescence (OSL), which potentially may be exploited for ionizing radiation dosimetry. Firstly, a red-stimulated luminescence was found in lutetium-aluminum garnet [ 8 ], and then, in our previous paper, we described infrared-stimulated luminescence of gadolinium aluminum-gallium mixed garnet Gd 3 Ga x Al 5−x O 12 (GGAG:Ce) [ 9 ]. When stimulated with IR at about 870 nm, the previously irradiated GGAG:Ce crystals exhibit very strong luminescent emission in the range of 500–600 nm, which is typical for Ce 3+ emission in garnets.…”
Section: Introductionmentioning
confidence: 99%
“…In general, some of these clustering centers may have excitation (absorption) spectra in the IR range. Taking into account that the intensity of IR OSL usually depends on the dopant concentration [ 8 , 9 ], the formation of pair centers with the participation of YAG host defects and Ce 3+ ions was not excluded as well. Identification of the nature of such centers is a hot topic and such research with the use of theoretical calculation [ 15 , 16 ], advanced optical methods [ 19 , 20 ], and radio-spectroscopic investigations [ 25 ] is performed on various garnet compounds.…”
Section: Introductionmentioning
confidence: 99%